The Effect of Ginger Extract on Reducing Dysmenorrhea Pain in Adolescents - Meilani, Sielfi Lutfia; Kusumastuti, Diah Andriani; Kulsum, Ummi (Yayasan Pendidikan Bukhari Dwi Muslim, 2025)
Purpose: This study aims to analyze the effect of ginger extract consumption on reducing dysmenorrhea pain in adolescent girls. The research is based on the hypothesis that ginger extract, due to its anti-inflammatory properties, significantly decreases menstrual pain intensity and provides a safe non-pharmacological treatment alternative. Research Method: The study employed a quasi-experimental design with a one-group pretest-posttest approach. The population consisted of 406 female students at SMP Negeri 2 Gebog, with a sample of 70 respondents selected using the Slovin formula. Data were collected through pain scale assessments before and after administration of ginger extract. Analysis was conducted using the Kolmogorov-Smirnov normality test and the Wilcoxon signed-rank test, as the data exhibited a non-normal distribution. Results and Discussion: Findings revealed a significant reduction in dysmenorrhea pain levels after consuming ginger extract, with a p-value of 0.000 (<0.05). Before the intervention, most respondents reported moderate to severe pain, whereas after the intervention, the majority experienced mild pain or no pain. This confirms the hypothesis and aligns with previous studies highlighting the effectiveness of ginger extract in reducing menstrual pain. Implications: The results suggest that ginger extract can be promoted as a low-cost, accessible, and safe alternative to manage dysmenorrhea among adolescents. Future research should consider larger samples, control groups, and long-term effects to strengthen generalizability.